Toilet training in children with certain developmental disorders - Đurić-Zdravković, Aleksandra; Rapaić, Dragan (Specijalna edukacija i rehabilitacija, 2023)
Mastering toilet training skills in childhood is considered an important developmental determinant. Acquiring proper toilet skills in children with developmental disorders is often delayed. The aim of this paper is to present possible problems that occur in children with intellectual disability, autism spectrum disorder, and cerebral palsy during toilet training, as well as to indicate the interventions that have proven to be effective in this domain. The paper points out the specifics of each of the treated clinical pictures regarding mastering toilet training skills. Behavioral interventions were specially addressed, and it was emphasized that they should be individualized based on the physical limitations and cognitive status of a child. Effective interventions include reinforcement, prompting, extinction, demonstrations, visual schedules, and others derived from treatment programs for children with developmental disorders.
Keywords: toilet training; continence; developmental disorders